Letter: association between medication use and microscopic colitis—selection of controls matters. Issue 10 (26th October 2021) - Liu, Yuanbin; Chen, Mingkai
LINKED CONTENT: This article is linked to Sandler et al paper. To view this article, visit https://doi.org/10.1111/apt.16594